Experimental investigation of the cyclic response of double curved surface sliders subjected to radial and bidirectional sliding motions. Issue 117 (February 2019) - Furinghetti, Marco; Pavese, Alberto; Quaglini, Virginio; Dubini, Paolo
Abstract: In the present work the experimental response of the Curved Surface Slider (CSS) is investigated through an experimental campaign, carried out on a full-scale prototype subjected to both unidirectional and bidirectional tests. The aim of the study is to assess the effect of vertical load, speed and sustained motion on the frictional response of the device and to compare results returned by different displacement trajectories. In order to perform a quantitative evaluation, a mathematical expression to model the decay of the coefficient of friction as a function of energy dissipation is proposed and calibrated upon experimental data. Though at low vertical load non-negligible discrepancies between unidirectional and bidirectional orbits were noticed, the CSS device shows consistent behaviour as the applied load, and consequently the dissipated energy, are increased. The results allow to draw some guidance for the estimation of the design variation range of the friction coefficient of Curved Surface Slider devices used to perform bound analyses. Highlights: At high contact pressure values 1D and 2D frictional responses are comparable. At low vertical loads 2D motions lead to higher frictional responses than 1D cases. The frictional decays due to sustained motions for 1D and 2D cases are comparable. The lowest friction is reached at high pressure and velocity under sustained motion. The highest friction occurs at low pressure and high velocity under short motion.